Historical trends in modifiable indicators of cardiovascular health and self-rated health among older adults: Cohort differences over 20 years between the Berlin Aging Study (BASE) and the Berlin Aging Study II (BASE-II) - Maximilian König; Johanna Drewelies; Kristina Norman; Dominik Spira; Nikolaus Buchmann; Gizem Hülür; Peter Eibich; Gert G. Wagner; Ulman Lindenberger; Elisabeth Steinhagen-Thiessen; Denis Gerstorf; Ilja Demuth (PLOS ONE, 2018)
Background: The last decades have seen great advances in the understanding, treatment, and prevention of cardiovascular disease (CVD). Although mortality rates due to CVD have declined significantly in the last decades, the burden of CVD is still high, particularly in older adults. This raises the question whether contemporary populations of older adults are experiencing better or worse objective as well as subjective health than earlier-born cohorts. The aim of this study was to examine differences in modifiable indicators of cardiovascular health (CVH), comparing data obtained 20 years apart in the Berlin Aging Study (BASE, 1990–93) and the Berlin Aging Study II (BASE-II, 2009–2014). Methods: Serial cross-sectional analysis of 242 propensity-score-matched participants of BASE (born 1907–1922) and BASE-II (born 1925–1942). Body mass index (BMI), blood pressure, total cholesterol, glycated hemoglobin (HbA1c), diet, smoking and physical activity were operationalized according to the “Life's simple 7“(LS7) criteria of the American Heart Association. Results: 121 matched pairs were identified based on age, sex, and education. In the later-born BASE-II sample, the mean LS7 score was significantly higher than in the earlier-born sample (7.8±1.8 vs. 6.4±2.1, p<0.001), indicating better CVH. In detail, diet, physical activity, smoking, cholesterol, and HbA1c were more favorable, whereas blood pressure was significantly higher in individuals from the later-born cohort. BMI did not differ significantly between the two matched samples. Notably, despite better CVH, later-born individuals (BASE-II) reported lower self-rated health, presumably because of higher health expectations. Conclusions: Overall, cardiovascular health was significantly better in the later-born cohort, but several notable exceptions exist.
Keywords: 330